Detection of Starch Adulteration in Local Soft Cheeses and Commercial Marketer for International Companies Marketing in Kirkuk City Iraq - Taha, Muna Hashim (American Journal of Bioscience and Clinical Integrity, 2026)
This study aims to investigate the prevalence of starch adulteration in local soft cheeses (traditionally known as "Arab Cheese") and commercial brands for international companies like Kerry, Anchor, Puck, and others available in the central market within Kirkuk city, north of Iraq. Despite the nutritional importance of dairy, economic fraud through the addition of thickeners is a growing concern. This study included 34 samples, divided by 17 samples from different commercial sources in market and 17 samples local soft cheeses (traditionally known as "Arab Cheese") Using a qualitative chemical approach centered on the Iodine-Starch reaction and quantitative Analysis by use (Spectrophotometry method), this research screens samples collected from diverse geographical areas in Kirkuk city November2024 to April 2025. Based on recent regional data, The results showed high starch detection rates of up to 35.3% samples contain starch in local soft cheese by using direct chemical examination and 35.3% from samples are samples showed no color change this detecting to absence of starch and 29.4% are slight color change this detecting to no present small amount of starch, In contras cheese commercially marketed where 52.9%of samples positive for starch, 29.4% samples contained trace amounts or no starch and 17.6% have medium of starch. This study provides critical insights into food safety and consumer protection in Northern Iraq.